Legacy III Project - Hoolihan, Daniel D. (IEEE electromagnetic compatibility magazine, 2024)
Progress continues on the Legacy III project of the History Committee of the EMC Society. As explained in previous issues of this magazine, the Legacy III project is digitizing the EMC European EMC Conferences. This includes the Zurich EMC Symposiums from 1975 to 2005, the EMC Europe International EMC Conferences from 1994 to 2010, and the Wroclaw, Poland, International Symposiums from 1972 to 2006. The project will digitize and upload the referenced symposiums to IEEE Xplore. The project was approved and funded by the Board of Governors of the EMC Society in 2024. It was a project that was under discussion and planning for almost 10 years. The IEEE eXpress Conference Publishing Department was selected to digitize and prepare for display on Xplore the hundreds of European papers published in the last fifty years.